Investigation of the microscopic properties of natural structured clay - Ning, Di; Ma, Qingshan; Ge, Weiya; Shao, Zefei; Lei, Ting; Xing, Huaixue (Frontiers in Earth Science, 2023)
Conducting quantitative research on the microstructure of soft clay can reveal the essence of its soil mechanical behavior, which is of important practical significance for geological disaster risk assessment and prevention. To quantitatively investigate the microscopic properties of natural structured clay, soft clay soils from various sedimentary environments in the Hangzhou Estuarine Bay area were chosen as the research subject in this study. Subsequently, a comprehensive investigation into the microstructure of clay was conducted, involving X-ray phase analysis and SEM imaging analysis. The results revealed the following: (1) In comparison to the deep clay deposited in fluviallacustrine environments, the shallow mucky clay in marine sediments has a higher clay mineral content, accounting for 48%. Illite makes up the majority of it, with minor levels of kaolinite and montmorillonite being present. (2) The shallow mucky clay in the Hangzhou Estuarine Bay area had a typical agglomerate-flocculated structure. In contrast, the deeper clay showed a flocculated structure with less uniform particle sizes, strong stacking randomness, poor directional alignment of soil pores, and tends to form arrangements where edges are adjacent to faces or edges are adjacent to other edges.(3) Compared to the deep clay deposited in fluvial-lacustrine environments, the marine-deposited shallow mucky clay displayed orderly pore arrangements, strong directional alignment, significant pore shape variability, and minimal pore size changes between adjacent pores. The microstructure of soil plays a crucial role in determining the physical, mechanical, and other engineering properties of the soil. And this study provides insightful information about the relationship between clay microstructure and geotechnical characteristics in Hangzhou and the surrounding areas.